Phase-Field Simulation of γ′-Co3 (Al, W) Evolution Kinetics with Antiphase Boundaries in Co-Based Monocrystal Superalloys - Ju, Yinfei; Li, Yongsheng; Shi, Shujing; Sang, Peng; Wang, Huiyu; Long, Hongli (Frontiers in Materials, 2022)
Antiphase boundaries (APBs) of L12 ordered γ′-Co3(Al, W) precipitates has an essential effect on the high-temperature strength of Co-based monocrystal superalloys. In this work, the antiphase boundaries and its effects on the evolution kinetics of γ′ phase are studied with the phase-field model. The formation of antiphase boundaries between γ′ phase with different crystallographic variants induces a sharp increase in free energy, the width of APBs measured by the edge-to-edge distances of γ′ phase is consistent with the experimental results of superalloys. And a coupling behaviors of Oswald ripening and APB’s migration in the coarsening of γ′ phase is revealed. Besides, compared with the single-domain γ′ phase, the volume fraction of γ′ phase with four antiphase domains is lower, the time exponent of the particles number density of γ′ phase at the steady coarsening stage changes from – 0.99 of single domain to – 0.8 of APBs. The results show that the high-energy APBs can reduce the coarsening rate of the γ′ phases, which is significant in the microstructure and composition designing of the ordered precipitates with APBs in Co-based superalloys.